2017
DOI: 10.21093/di.v17i1.649
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Feedback on Writing Quality of College Students with Different Cognitive Styles

Abstract: Feedback provision in the process of writing has been believed that it is beneficial. However, different strategies of providing feedback may affect differently on writing quality of students. This study aimed at investigating the effect of different feedback provision on the writing quality of students having different cognitive styles. By conducting an experimental through a factorial research design, fifty-five of the fourth semester English students of STAIN Kediri were involved in this study. For analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
0
18
2
1
Order By: Relevance
“…Ferris (Ferris, 1999), however, keeps arguing that there have been a lot of research findings which show that error corrections can and do help. Though the debate on its effectiveness is still going on until these days, the results remain inconclusive (Alimohammadi & Nejadansari, 2014;Bitchener & Knoch, 2009;Bitchener, Young, & Cameron, 2005;Diab, 2005;Hyland, 1998;Hyland & Hyland, 2006a;Jusa & Kuang, 2016;Karim & Nassaji, 2015;Maharani, 2017;Storch, 2010;Vyatkina, 2011;Wahyuni, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ferris (Ferris, 1999), however, keeps arguing that there have been a lot of research findings which show that error corrections can and do help. Though the debate on its effectiveness is still going on until these days, the results remain inconclusive (Alimohammadi & Nejadansari, 2014;Bitchener & Knoch, 2009;Bitchener, Young, & Cameron, 2005;Diab, 2005;Hyland, 1998;Hyland & Hyland, 2006a;Jusa & Kuang, 2016;Karim & Nassaji, 2015;Maharani, 2017;Storch, 2010;Vyatkina, 2011;Wahyuni, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the importance of giving feedback on students writing is equal to the importance of doing revisions and/or editing in the writing process. Feedback given is as a source of information about the students' strengths and weaknesses on their writing improvement (Wahyuni, 2017).…”
mentioning
confidence: 99%
“…Short-term effects are related to improvement from one draft to another whereas long-term effects refer to improved performance in new tasks (Ferris, 2006). Another study conducted by Wahyuni (2017) concluded that WCF did not have a significant impact on the grammatical accuracy of written productions of low-proficiency learners; however, the author recognized that the study had limitations like confusion when interpreting feedback and student's proficiency level, lack of time to solve students' doubts, and teacher's inexperience for teaching writing. Lastly, the main opponent of WCF, Truscott (1996), advocated for the inefficacy of WCF and determined that it is harmful for students as it may produce students' demotivation to keep writing as they would avoid making errors.…”
Section: Written Corrective Feedbackmentioning
confidence: 99%
“…Ferris (2010) calls for WCF as the means to make errors stand out for students in order to amend them; hence, avoiding error fossilization and allowing development of linguistic competence (Ferris, 2004). In fact, research evidence (Ferris, 2006;Hosseiny, 2014;Farshi & Safa, 2015;Atmaca, 2016;Westmacott, 2017;Nematzadeh & Siahpoosh, 2017;Wahyuni, 2017) shows that WCF has been used in its different strategies by teachers to correct written errors and help learners polish their writing skill. Despite the existence of studies presenting a positive impact by WCF, there are still opponents to error correction.…”
Section: Introductionmentioning
confidence: 99%